Progress of the Plan: A short Survey of Working of the Five Year Plan from April 1951 to September 1953 Government of India Planning Commission - Planning Commission (Planning Commission, 1951)
The objectives of the Five Year Plan have been set out in detail in the Report. Briefly, these objectives aim at initiating a process of development which will raise living standards and open out to the people new opportunities for a richer and more varied life. This implies:-(i) the provision of increased employment and production by the most efficient utilization of the resources of the country; and (ii) the achievement of the largest measure of social justice possible.
Government of India Planning Commission